Water Quality Assessment of Simav River (Susurluk Basin/Turkey) According to Seasons and Stations - ÇİÇEK, Nezire Lerzan and GÜÇLÜ, Salim Serkan and ERDOĞAN, Ömer and KÜÇÜK, Fahrettin (International Journal of Computational and Experimental Science and Engineering, 2023)
Susurluk Basin is under intense pressure from domestic, industrial wastes and agricultural activities. In this study, the effect of environmental factors on Simav Stream, one of the important rivers of the Susurluk Basin, was tried to be determined. In this purpose water samples were taken from 13 satation seasonally in 2014-2015, and water quality parameters including dissolved oxygen, saturation, temprature, pH, electrical conductivity, salinty, turbidty, calcium, magnesium, total hardness, nitrite nitrogen, nitrate nitrogen, ammonium nitrogen, phosphate phosphorus, total phosphor, chloride, bicarbonate, carbonate, were determined in this samples. The results were compared with the limit values specified in the national and international quality criteria. According to the Surface Water Quality Regulation (SWQR), the upper parts of the river were less polluted (II. quality) and the middle and lower parts were polluted water (III. quality). As a result of the research, it has been observed that the middle and lower reaches of the Simav Stream are under the pressure of intense agricultural, animal husbandry and pollution from domestic and industrial waste waters. It was determined that the pollution pressure started to increase in the upper part as well.